Discourse peculiarities of computer games - Shevchenko, Viacheslav D.; Galashov, Alexander V. (Aktualʹnye problemy filologii i pedagogičeskoj lingvistiki, 2024)
The present paper refers to the current problem of semiotic signs’ specifics in the context of gaming discourse based on texts from action first-person shooter game Ultrakill developed by Finnish creators. The problem is relevant due to the influence that computer games have on people’s mind – in particular on the minds of the younger generation. Moreover, the study will help to understand the linguistic mechanisms of the impact of video games on players. The study used methods of semantic analysis, semiotic analysis, observation and description techniques. As a result, the research revealed that developers use intertextual units to create patterns that are familiar to the player, but which at the same time have new characteristics. While 66% of all intertext is universally known, obscure allusions play an important role in creating associations for the recipient as well, which proves the importance of intertext in video game discourse. Well-known allusions play a role in creating semantic images in the game, while the lesser known intertext has easy to understand semes that could provoke the player to action in game. The research identified the following types of intertext: allusions to songs, music albums, other games, myths, the Bible and literature. The synthesis of intertext and author’s text in level names gives the player an idea of the upcoming challenges without informing of the level context, and in some cases even intriguing the player. The combination of borrowings and original semiotic units in the names of characters creates images that are familiar to the player, but at the same time, it creates properties that are specific to this particular game. Dialogues are mainly inherent in this genre, but the conversations also have deviations from this genre, which is also done in order to affect the player – the author gives the recipient a familiar behavior pattern in order to replace it afterewards, causing cognitive dissonance to the player. Conclusions are drawn about the discourse mechanisms in video games, how they affect the player and for what purpose the developer uses one or another linguistic technique.